Investigation of Tamarind Seed Oil biodiesel with aluminium oxide nanoparticle in CI engine. (2021) - Shaisundaram, V.S.; Chandrasekaran, M.; Muraliraja, R.; Shanmugam, Mohanraj; Baskar, S.; Bhuvendran, Arun
Abstract: Because of increasing automobiles, power plants and factories, increasing of this automobiles, power plants produce the more emissions like CO, HC and NOx. So that the world is searching for the alternative fuel, which will not create any harm to the environment and also it would be less in cost. Biodiesel is one of the main solutions to the global energy crisis. In this present work studied the performances and emission characteristics of Tamarind Seed Oil Bio-diesel (TSO). Use of additives for better combustion characteristics to the biodiesel. The blends of Tamarind Seed oil (TSO) with the additives Aluminum oxide (Al2 O3 ) are B10 + 20 PPM Al2 O3, B20 + 20PPM Al2 O3, B30 + 20 PPM Al2 O3 . This blends were analyzed and their performance and emissions characteristics compared with performance and emission characteristics of diesel. Tests were carried out over entire range of engine operation at varying conditions of load. The engine exhaust gas emissions are reduced with increase biodiesel concentration.